A QUANTUM CHEMICAL INVESTIGATION OF N1-SUBSTITUTED 1,2,4-TRIAZOLE - Vesna Dimova, Mirjana S. Jankulovska, Milena Jankulovska (RAD Conference Proceedings, 2018)
The molecular conformations and electronic properties of a set of five N1-(o/p-substituted phenyl)aminomethyl-1,2,4-triazole derivatives (PhAMT) were investigated by two semiempirical methods: AM1 and PM3. Characteristic bond lengths (N1-C2, C2-H6, C2-N3, N3-N4, N4-C5, C5-H7 and N1 - C5), angles (N1-C2-N3, C2-N3-N4, N3-N4-C5, N4-C5-N1 and C5-N1-C2) and atomic charges (N1, C2, N3, N4, C5, H6 and H7) for 1,2,4-triazole core were calculated and discussed in accordance with literature data for similar 1,2,4-triazole compounds. The EHOMO and ELUMO values, total energies, the heats of formation and dipole moments values were calculated, as well. The discussion was performed in accordance with the type and position of a substituent present in the aromatic core.
Keywords: AM1, PM3, atomic charge, bond length, dipole moment, EHOMO, ELUMO, heat of formation, 1,2,4- triazole derivatives